PENGARUH EFIKASI DIRI AKADEMIK TERHADAP HASIL BELAJAR MATEMATIKA TENTANG SOAL CERITA OPERASI HITUNG CAMPURAN - Ratih Yusnimartika; Eriva Syamsiatin; Sri Indah Pujiastuti (Jurnal Ilmiah Visi, 2013)
The purpose of this study is to determine the effect of academic self efficacy on math learning outcomes particularly in solving mixed word problems. The study was conducted at SDN Pinang Ranti 04 Pagi, East Jakarta, in January 2013. Employing ex-post facto method, the study selected 32 students of the third grade. The data were collected using questionnaires and descriptive test and analyzed by t-test for the hypothesis. The results indicate positive significant influence of academic self efficacy on the learning outcomes in math mixed word problems. The implications of this research is high academic self efficacy needs to have as it gives effect to the students’ academic success. The students can enhance their academic self efficacy by increasing self efficacy experiences, observations on the other people’s success. The teachers and parents can help the students to their academic self efficacy by providing encouragement. The students’ learning outcomes can be influenced by internal and eksternal factors.